Agricultural Waste and Residues - Aladjadjiyan, Anna (IntechOpen, 2018)
This book is dedicated to the reuse of waste and residues from the agricultural sector. Plant residues, as well as animal manure and residues from animal breeding, contain useful elements that can be processed for production of fertilizers, compost for soil recultivation, and biofuels. The emerging energy and resources crisis calls for development of sustainable reuse of waste and residues. This book contains eight chapters divided into four sections. The first section contains the introductory chapter from the editor. The second section is related to the preparation of fertilizers and compost for soil amelioration from agricultural residues and waste water. The third section considers the use of agricultural waste for solid biofuels and biogas. The fourth section discusses sustainability and risk assessment related to the use of agricultural waste and residues.